Comparative Health Information Management - Peden, Ann H. (Thomson Delmar Learning, 2005)
Explore the many paths your career may take in the fast-changing world of health information management with COMPARATIVE HEALTH INFORMATION MANAGEMENT, THIRD EDITION. This unique textbook covers health care practice and information management in a wide variety of settings, from free-standing and hospital-based ambulatory clinics to veterinary offices and correctional facilities, and the challenges associated with managing the information flow among various sites